Penyalinan Naskah Melayu di Palembang; Upaya Mengungkap Sejarah Penyalinan - Rukmi, Maria Indra (UI Scholars Hub, 2005)
In Palembang manuscripts are known to be available originating in the Palembang Palace as well as individual collection. This paper discusses the tradition of copying manuscript in Palembang, beginning with the historical background of Palembang, continuing with Malay manuscript copying in Palembang, and with a limited information on the content of the manuscript. Cultural diversity in Palembang where Javanese, Chinese, Arab elements are found, as well as those of the aristocrats and the common people, have impacted on the social lives of the people of Palembang. This diversity is reflected in the manuscripts that have been preserved, including those originating in the Palace, the Arab village, and the local residents.